2014
DOI: 10.1016/j.ijsu.2014.05.066
|View full text |Cite
|
Sign up to set email alerts
|

TERT promoter mutation in resectable hepatocellular carcinomas: A strong association with hepatitis C infection and absence of hepatitis B infection

Abstract: Our study indicated that the TERT promoter mutation frequently occurred in HCV-associated HCCs. The absence of Hepatitis B infection was significantly associated with the TERT promoter mutation. These findings suggest that various etiological factors may be involved in differing mechanisms to preserve telomeres during the carcinogenesis of HCCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
62
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 30 publications
11
62
4
Order By: Relevance
“…Specifically, they were observed in 57% of preneoplastic lesions and in 30% of stage I HCCs[165], indicating that TERT promoter mutations occur early during malignant transformation and persist throughout tumor progression. These findings have been further confirmed by two recent studies using exome or DNA sequencing of liver tumor samples in which TERT promoter mutations occurred early during hepatocarcinogenesis[106,164]. In addition, when hTERT mRNA was measured via real-time quantitative RT-PCR, the hTERT mRNA levels were found to be increased in association with the progression of hepatocarcinogenesis, and most HGDNs strongly expressed hTERT mRNA at levels similar to those in HCC samples[168].…”
Section: Somatic Mutations In Hccmentioning
confidence: 59%
See 2 more Smart Citations
“…Specifically, they were observed in 57% of preneoplastic lesions and in 30% of stage I HCCs[165], indicating that TERT promoter mutations occur early during malignant transformation and persist throughout tumor progression. These findings have been further confirmed by two recent studies using exome or DNA sequencing of liver tumor samples in which TERT promoter mutations occurred early during hepatocarcinogenesis[106,164]. In addition, when hTERT mRNA was measured via real-time quantitative RT-PCR, the hTERT mRNA levels were found to be increased in association with the progression of hepatocarcinogenesis, and most HGDNs strongly expressed hTERT mRNA at levels similar to those in HCC samples[168].…”
Section: Somatic Mutations In Hccmentioning
confidence: 59%
“…The frequency of TERT promoter mutations in HCC varies substantially across the different geographical regions studied. For example, cases of HCC with TERT promoter mutations have been reported from the United States[161], Europe[104,158,162], Africa[163], and East Asia (except for Japan)[103,104,164-166], with mutation frequencies of 44%, 47%-59%, 53%, and 20.7%-38.8%, respectively. These data indicate that TERT promoter mutations are less frequent among Asian patients with HBV-related HCC than among those with HCV-related HCC.…”
Section: Somatic Mutations In Hccmentioning
confidence: 99%
See 1 more Smart Citation
“…Following stratification of variables, including TL, TERT promoter mutation status exhibited no prognostic significance (data not shown). Certain recent studies demonstrated no difference in TERT expression compared with the presence of TERT promoter mutations (21,22). These reports indicate that tumor cells without TERT promoter mutations may have other mechanisms for activating TERT expression and changing TL.…”
Section: Tert Promoter Status ---------------------------------------mentioning
confidence: 79%
“…Preferential integration of the HBV genome in the regions near or in the TERT gene has also been reported in five of the six HBV-HCC NGS studies [16,19,108110]. Interestingly, higher rates of mutations in TERT (46% in HCV-HCC vs 16% in HBV-HCC) [111] and CTNNB1 (62.5% in HCV-HCC vs 37.5% in non-HCV-HCC) [15] were reported in HCV-associated HCC. Recently, it was suggested that TERT is the gate keeper of HCC [112].…”
Section: Hcc-associated Cancer Pathways and Candidate Dna Biomarkers Fomentioning
confidence: 87%